PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MAHASISWA BIOLOGI - Ramadansur, Rahmat; Eriyanti, Ribut Wahyu; Hudha, Atok Miftachul (Universitas Lancang Kuning, 2023)
Understanding is one of the bases for developing learning models, with an emphasis on indicators of learning understanding. One alternative when learning can enable increased understanding of concepts by using the CTL learning model. The purpose of this study was to determine the effect of CTL on increasing the ability to understand biology students' concepts. The type of research used was a quasi-experimental design in the form of a nonequivalent control group design. The quasi-experimental group has a control group, but cannot fully function to control external variables that affect the implementation of the experimental group. The research design uses the pretest method before the lesson starts, then is given treatment using the CTL learning model, and ends with a posttest to measure differences in the level of students' conceptual understanding abilities at each meeting. The form of this research is quantitative. The results showed that there was an effect of using the Contextual Teaching and Learning (CTL) learning model on students' understanding of concepts with a pretest control class score of 65 and a posttest of 75. Meanwhile, the pretest and posttest experimental class scores were 80